Pelatihan Pembuatan Prototype Pintu Otomatis Berbasis Arduino di SMK Mambaul Ulum Paiton - Sulistiyanto; Zainul Rahman; Abi Manyu (Insan Kreasi Media, 2022)
SMK Mambaul Ulum is one of the educational institutions under the auspices of the Mambaul Ulum Foundation sukodadi village paiton subdistrict. The room in SMK MAMBAUL ULUM such as: Office, Lab, Library still uses manual doors. The solution to this problem is to conduct the introduction and training of automated door systems. This system can only be used if you have an access card registered on that system. This form of service activity is training consisting of 3 main stages, namely location surveys and socialization, training, inauguration / evaluation. Based on the results of the activity, it can be concluded that students' knowledge of the automatic door system increases which is characterized by student enthusiasm in participating in the training.